„INTERNET SYMPHONY No. 1”: RETHINKING THE ORCHESTRA AS A VIRTUAL COMMUNITY - ŢIPLEA TEMEŞ, Bianca (Studia Universitatis Babes-Bolyai Musica, 2014)
The article outlines, from a historical and sociological perspective, the evolution of the Symphony Orchestra from its origins (Vingt-quatre violons du roi) to its most recent incarnation as a product of current information technology: the YouTube Symphony Orchestra. The project recreates the ensemble as a virtual community, exploiting advances in technology to convert the artistic act into a transmedia product; it includes a selection process by video and e-mail, and online educational assistance for the musicians, followed by the video ’mash up’ of selected candidates, constituting the final version of Tan Dun’s piece Internet Symphony No. 1. Not being a single case, it has a ‘vocal’ equivalent in Eric Whitacre’s Virtual Choir, which is in fact a mix of 185 tracks individually recorded. The interaction between musicians is redefined within a multiplicity of contexts, providing a new framework for conceptualizing the artistic act as a matrix of integrative “multi-track creativity”.